Energy management of portable power supply II - Tay, Edmund Si Han (Nanyang Technological University, 2024)
Renewable energy has gained traction over recent years, which has led to a very huge increase in the amount of renewable energy adoption worldwide with Photovoltaic (PV) and wind energy leading the transition due to their potential and availability. Besides having PV and wind as renewable energy sources, the system would also consist of components like power electronic converters and battery energy storage system (BESS), to allow for energy conversion and storage. Existing BESS are huge which does not allow for portability. It would be very difficult to establish an electrical connection from the BESS to remote locations, especially during times of emergencies like natural disasters where having a stable electricity connection would be crucial in rescue operations. The project aims to design and develop a portable power supply for remote low-voltage applications. Maximum Power Point Tracking (MPPT) will be used to ensure that maximum PV and wind energy will be harnessed. A Model Predictive Control (MPC) algorithm will be developed for the inverter to achieve energy conversion to meet the load requirements. An Energy Management System (EMS) will be developed to manage the PV, wind, and battery to deliver constant electricity to the load demands and apply load shedding in times when energy generation is low due to the intermittent nature of renewable energies. The design and simulation of the system will be done in PLECS software. The simulation results are exported from PLECS and then imported to MATLAB which would plot and display the simulation results.